Показники функціонального стану шкіри у щурів при нанесенні гелю «Лізостом» = Functional indices of skin in rats with applying the gel "Lizostom" - Kavushevska, N. S.; Bereznyakova, A. I.; Zhemela, O. D. (Journal of Education, Health and Sport, 2016)
Kavushevska N. S., Bereznyakova A. I., Zhemela O.D. Показники функціонального стану шкіри у щурів при нанесенні гелю «Лізостом» = Functional indices of skin in rats with applying the gel "Lizostom" Journal of Education, Health and Sport. 2016;6(9):917-921. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166354 http://ojs.ukw.edu.pl/index.php/johs/article/view/3992 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. УДК 616. 31002:616. 311. 2002:616. 314. 17008. 1:61608 ПОКАЗНИКИ ФУНКЦІОНАЛЬНОГО СТАНУ ШКІРИ У ЩУРІВ ПРИ НАНЕСЕННІ ГЕЛЮ «ЛІЗОСТОМ» Н. С. Кавушевська*, А. І. Березнякова*, О. Д. Жемела** *Національний фармацевтичний університет, м. Харків ** Харьківський національний університет ім. В. Н. Каразіна Резюме В результаті вивчення показників функціонального стану шкіри щурів встановлено відсутність пошкоджую чого впливу та запальних процесів під дією гелю «Лізостом» Ключові слова: шкіра, лізоциму гідрохлорид, гель FUNCTIONAL INDICES OF SKIN IN RATS WITH APPLYING THE GEL "LIZOSTOM" N. S. Kavushevska*, A. I. Bereznyakova*, O. D. Zhemela** *National University of Pharmacy, Kharkiv ** V. N. Karazin Kharkiv National University Summary As a result of studying the functional performance of the skin of rats found no damage what influence and inflammation under gel "Lizostom" Keywords: leather, lysozyme hydrochloride gel